DISCOURSES ON THE COSTA RICAN NATIONAL CUISINE AND THE CULTURAL RELOCATING OF GUANACASTE - Nikolić, Mona (2015)
In recent years, due to the growing transnationalization of consumption, national cuisine has been given ever more consideration in Costa Rica. Apart from making explicit the relevance of the national cuisine as a marker of national identity, the national cuisine’s discussion gives proof of the renegotiation of cultural and regional differences taking place in the current context of this cuisine’s formation. Studying the formation of a national cuisine, it is relevant to consider its impact on regional and ethnic cuisines. For the marginalization of the provinces of Guanacaste and Limón and their habitants in the discourses on Costa Rican national identity in the past, it is particularly interesting to contemplate these regional cuisines.This article focuses on the way the current concept of a Costa Rican National Cuisine is discussed on a local level, in Guanacaste. Drawing on results of my fieldwork conducted in 2011, I will show that the construction of a national cuisine is accompanied by a rise of the local cuisine’s importance as a marker of regional identity. I hold that Guanacastecan identity, as expressed in this discussion can be understood as resistance identity and that the discussion motivates a renegotiation of regional, national and cultural belonging.